Benin : Technical Assistance Report-Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
This report provides an evaluation of fiscal transparency practices (FTE) in Benin according to the standards defined by the IMF's Fiscal Transparency Code. The evaluation focuses on 36 principles covering three pillars of the Code: (I) fiscal reporting; (II) fiscal forecasting and budgeting; and (III) fiscal risk analysis and management. To take account of different levels of institutional capacity in each country, the Code distinguishes three levels of practices for each principle: basic, good, and advanced. A practice is considered "not met" if it has not met the Code's requirements for basic level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy